Experimental investigation of heavy metal accumulation in tissues of stone loach noemacheilus barbatulus (L.) and rainbow trout oncorhynchus mykiss (walbaum) exposed to a model mixture (Cu, Zn, Ni, Cr, Pb, Cd) - Idzelis, Raimondas Leopoldas; Kesminas, Vytautas; Svecevičius, Gintaras; Venslovas, Albertas (Journal of Environmental Engineering and Landscape Management, 2010)
During experiment, fish were exposed to a heavy metal model mixture (Cu, Zn, Ni, Cr, Pb, Cd) for 14 days. Heavy metal concentrations corresponded to Maximum Permitted Concentrations (MPC) in surface waters. The amount of heavy metals in fish tissues was determined using atomic absorption spectrophotometry (AAS). Though both investigated fish species accumulated heavy metals with similar general intensity, the stone loach did it in the sequence gills > liver > muscle, and the rainbow trout ‐ conversely: muscle > liver > gills. Ni concentration in the stone loach muscle made 0.607 mg/kg and Pb concentration was 0.21 mg/kg, whereas Cd concentration in the rainbow trout muscle reached 0.45 mg/kg and exceeded the MPC indicated in the Lithuanian hygiene standard. These results coincide with the data of the heavy metal research into fish species from natural water bodies. Pb and Cd concentrations in fish tissues are the highest and frequently exceed the MPC. These findings urge for the constant control of the amount of heavy metals in fish.Sunkiųjų metalų kaupimosi šlyžio Noemacheilus barbatulus (L.) ir vaivorykštinio upėtakio Oncorhynchus  mykiss  (Walbaum) audiniuose  eksperimentiniai  tyrimai  veikiant  modeliniu  mišiniu (Cu, Zn, Ni, Cr, Pb, Cd)Santrauka. Bandomosios žuvys 14 par7 buvo veikiamos modeliniu sunkiųjų metalų mišiniu (Cu, Zn, Ni, Cr, Pb, Cd). Metalų koncentracijos atitiko jų didžiausias leidžiamas koncentracijas (DLK) paviršiniuose vandenyse. Sunkiųjų metalų kiekis audiniuose buvo nustatomas atominės absorbcijos spektrofotometriniu (AAS) būdu. Nors abiejų tirtų rūšių žuvų audiniuose sunkieji metalai kaupėsi vienodu intensyvumu, šlyžio audiniuose jie kaupesi tokiu eiliškumu: žiaunos > kepenys > raumenys, o vaivorykštinio upėtakio – atvirkščiai: raumenys > kepenys > žiaunos. Šlyžio raumenyse Ni koncentracija buvo 0,607 mg/kg, o Pb – 0,21 mg/kg , vaivorykštinio upėtakio raumenyse Cd koncentracija sieke 0,45 mg/kg ir viršijo Lietuvos higienos normoje nurodytaja DLK. Šie rezultatai sutampa su sunkiųjų metalų nuolatinės stebėsenos kontroliuojamų rūšių žuvyse iš natūralių vandens telkinių tyrimų duomenimis. Žuvų audiniuose Pb ir Cd koncentracijos yra didžiausios ir dažnai viršija DLK. Tokie rezultatai įpareigoja nuolat kontroliuoti sunkiųjų metalų kiekį žuvyse.Reikšminiai žodžiai: žuvys, toksiškumas, mitybinė grandis, eksperimentiniai tyrimai, higienos norma.Экспериментальное исследование накопления тяжелых металлов в тканях гольца  Noemacheilus  barbatulus  (L.) и радужной форели Oncorhynchus  mykiss  (Walbaum) при воздействии модельной смеси (Cu, Zn, Ni, Cr, Pb, Cd)Резюме. Подопытные рыбы в течение 14 суток подвергались воздействию смеси тяжёлых металлов (Cu, Zn, Ni, Cr, Pb, Cd) в предельно допустимых концентрациях (ПДК), предусмотренных для внутренних водоёмов. Количество тяжелых металлов в тканях рыб устанавливали при помощи атомной абсорбции спектрофотометрическим методом. Несмотря на то, что оба вида рыб накапливали металлы с одинаковой общей интенсивностью, голец их накапливал в следующей последовательности: жабры > печень> мышцы, а радужная форель – наоборот: мышцы > печень> жабры. В мышцах гольца концентрация Ni составила 0,607 мг/кг, Pb – 0,21 мг/кг, а в тканях форели концентрация Cd составила 0,45 мг/кг и превышала ПДК. Экспериментальные данные совпадают с данными, полученными в мониторинговых водоемах. Установлено также, что концентрация Pb и Cd в тканях зачастую прeвышаeт ПДК. Полученные результаты обязывают постоянно контролировать уровень тяжелых металлов в тканях рыб.Ключевые слова: рыбы, токсичность, пищевая связь, экспериментальный анализ, гигиеническая норма.First Publish Online: 27 Jun 2011